Screening, diagnosis and management of autism spectrum disorders amongst healthcare practitioners in South Africa - Matlou, M. J. (University of the Free State, 2021)
Background: There is a global increase in Autism spectrum disorders (ASD) prevalence, awareness and its effect on the burden of disease. It is crucial that ASD is recognized and diagnosed timeously for early intervention during the age of high neuroplasticity for optimal outcomes. We do not know if Health Care Practitioners (HCPs) in South Africa working in paediatric departments are able to diagnose and manage these children with complex medical needs. Objectives: This study was done to determine how paediatric HCPs in South Africa screen for, diagnose and manage autism spectrum disorders in both the public and private sector. Paediatric healthcare workers, general practitioners and primary level personnel are typically the first point of contact for family members concerned with ASD traits. Methods: A cross sectional descriptive analytical study design was conducted over a period of 11 months, from 1 March 2020 to 31 January 2021. An in-depth questionnaire was sent out via an electronic platform, namely Chatbot to eligible participants. A random sample of 116 completed questionnaires were captured on Google spreadsheets by Dekode IT Company and used for statistical analysis. Results: The majority of HCPs (70.7%) do not routinely screen children for ASD between 18-24 months as recommended by the American Academy of Paediatrics.10 Common methods used for screening ASD were; milestones, development and occasionally the checklist for Autism (CHAT)/Modified-CHAT. There was lack of knowledge about diagnostic tools used for ASD in 40% of HCPs that made ASD diagnosis. HCPs opted for developmental history, medical examination, unstructured behavioural observation, parental concern and DSM 5 criteria to make the diagnosis, which might under- or overestimate ASD statistics. Following the diagnosis 78.5% of HCPs referred patients to another discipline. Common referrals to speech therapists and occupational therapists for coordinated multidisciplinary assessment were noted. Hearing screen was a frequent investigation undertaken when making the ASD diagnosis. Other investigations occasionally used were CT/MRI, EEG, fragile X and genetic microarray analysis. Of the HCPs that managed ASD patients, less than 25% initiated treatment by prescribing risperidone followed by methylphenidate and valproate respectively. Supplements used were multivitamins, omega acids and Vitamin B6. Barriers to diagnosing and managing ASD identified in this survey were lack of experience, educational resources, referral centers, family support, specialists in the field, therapists, time and parental denial. In 85% of cases a HCP would provide information to the caregiver about autism. Conclusions: HCPs in SA lack knowledge, awareness, and training to diagnose and manage children with ASD. Autism is not screened for routinely or as recommended in practice. There is a lack of knowledge about the diagnostic tools to diagnose ASD. Not all suspected Autism cases were referred for multidisciplinary assessment and a hearing screen. There were multiple barriers contributing to making an early diagnosis of Autism noticed.
Dissertation (M.Med. (Paediatrics and Child Health))--University of the Free State, 2021
Keywords: Autism spectrum disorder (ASD); Autism; Screening; Diagnosis; Management; South Africa; Healthcare workers; Paediatrics